2003
DOI: 10.1034/j.1600-6143.2003.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Dosing in Pediatric Heart Transplant Patients is Related to CYP3A5 and MDR1 Gene Polymorphisms

Abstract: Tacrolimus is a substrate for P-glycoprotein (P-gp) and cytochrome (CYP) P4503A. P-gp is encoded by the multiple drug resistance gene MDR1 and CYP3A is the major enzyme responsible for tacrolimus metabolism. Both MDR1 and CYP3A5 genes have multiple single nucleotide polymorphisms. The objective of this study was to evaluate whether the MDR1 exon21 and exon26 polymorphisms and the CYP3A5 polymorphism are associated with tacrolimus disposition in pediatric heart transplant patients. At 3, 6 and 12 months post tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
174
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(193 citation statements)
references
References 42 publications
17
174
1
1
Order By: Relevance
“…The contribution of MDR1 genetic polymorphisms has also been extensively studied for the calcineurin inhibitors cyclosporine and tacrolimus, which show large interindividual differences in oral bioavailability. Though two studies in renal transplant patients found cyclosporine and tacrolimus dose requirement to be higher in individuals homozygous for the 3435T allele (44,45), two other studies investigating tacrolimus steady-state dose requirement found an opposite effect, with plasma levels being lower in the 3435CC group after 3, 6, and 12 months (46,47). A recent study investigating the effect of genetic polymorphisms in CYP3A4, CYP3A5, and MDR1 on the pharmacokinetics of cyclosporine and tacrolimus also found no evidence supporting a role for the MDR1 C3435T polymorphism in dose requirement of the two drugs, consistent with previous reports regarding cyclosporin A trough levels and MDR1 genotype (48,49).…”
Section: Impact Of Mdr1 Genetic Polymorphism On Drug Dispositionmentioning
confidence: 98%
See 1 more Smart Citation
“…The contribution of MDR1 genetic polymorphisms has also been extensively studied for the calcineurin inhibitors cyclosporine and tacrolimus, which show large interindividual differences in oral bioavailability. Though two studies in renal transplant patients found cyclosporine and tacrolimus dose requirement to be higher in individuals homozygous for the 3435T allele (44,45), two other studies investigating tacrolimus steady-state dose requirement found an opposite effect, with plasma levels being lower in the 3435CC group after 3, 6, and 12 months (46,47). A recent study investigating the effect of genetic polymorphisms in CYP3A4, CYP3A5, and MDR1 on the pharmacokinetics of cyclosporine and tacrolimus also found no evidence supporting a role for the MDR1 C3435T polymorphism in dose requirement of the two drugs, consistent with previous reports regarding cyclosporin A trough levels and MDR1 genotype (48,49).…”
Section: Impact Of Mdr1 Genetic Polymorphism On Drug Dispositionmentioning
confidence: 98%
“…No difference in cyclosporine and tacrolimus dose requirement [49] Renal transplant patients T-129C, C1236T, G2677T/A (Ala893Ser/Thr), C3435T Tacrolimus Higher tacrolimus dose requirement in carriers of the 2677T/A alleles [44] Pediatric heart transplant patients G2677T/A (Ala893Ser/Thr), C3435T Tacrolimus Higher tacrolimus blood levels at 6 and 12 months [47] Japanese women T-129C -Increased placental P-glycoprotein expression levels [22] Caucasian volunteers C1236T + G2677T/A (Ala893Ser/Thr) + C3435T…”
Section: Impact Of Mdr1 Genetic Variation On Expression and Function mentioning
confidence: 99%
“…3,6) The CYP3A5*3 genotype is well-known to be associated with the pharmacokinetics of tacrolimus in patients with liver, kidney and heart transplant. [17][18][19][20] Hepatic and intestinal CYP3A5 plays a significant role in the clearance of tacrolimus after oral administration in liver transplant patients. 4,5) However, a newly identified SNP in the CYP3A4 gene, CYP3A4*1G affects the pharmacokinetics of some drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the dose of tacrolimus is associated with CYP3A5 A6986G SNP [5][6][7]. Dose adjusted trough concentrations were 3 fold and 1.6 fold higher in mutants (G/G) than in heterozygous (A/G) patients for tacrolimus and Cyclosporine, respectively [8,9].…”
Section: Resultsmentioning
confidence: 99%